The pivotal role of water potential in phenology and seed germination of Abies spectabilis in the western Himalayan treeline region - Singh, Nandan; Mittal, Amit; Tewari, Ashish; Shah, Shruti; Wani, Zishan Ahmad; Siddiqui, Sazada (Frontiers in Forests and Global Change, 2024)
Abies spectabilis (East Himalayan Fir), a dominant timber-producing species in the Himalayas, plays a dynamic role in ecological balance and sustains various habitats across temperate to subalpine altitudes. Himalayan montane forests express signs of changes in the growth, regeneration, and population density of forest tree species due to ongoing climate change, including its upper distribution limit. The research was conducted at 30°11´02˝N and 79°39´36˝E, ranging from 3100 to 3500 m asl elevation in the treeline ecotone of western Himalaya. The study presents a comprehensive perspective on how water availability and its intricate interactions with climatic and ecological variables shape the dynamics of treeline ecosystems. The study's phytosociological analysis of treeline sites revealed the complex interplay between species composition, adaptability, and regeneration potential. The eco-physiological aspects of water balance were thoroughly explored, underscoring how plants employ various strategies to cope with changing water availability. The soil moisture content ranged from 32.17 to 73.50%. The dynamic nature of water potential (pre-dawn (ΨPD) and mid-day (ΨMD)) across seasons and years reflects and varies between -0.13 and -1.25 MPa, the species' ability to adjust and manage water balance according to environmental shifts. Osmotic potential at full turgor varied from -0.72 to -1.77MPa, these adjustments are crucial for key life cycle events of vegetative and reproductive phases of species. The strong correlation of water potential (Ψ) and phenophases emphasizes the importance of water status in regulating these vital processes. Furthermore, the study delved into the maturation and germination processes, highlighting the significance of Ψ and moisture content in seed development and germination success. The maximum germination of 46.33% was observed when the seed moisture content was 30.90±3.11%. The observed correlations between cone characteristics and seed parameters indicate the existence of trade-offs that impact seed size, weight, and germination capacity, contributing to the overall fitness of the species.